Empowering minority voices: how inclusive teaching and support foster multicultural learning - Alhassan, Awal Mohammed; Christensen, Margrethe Hall; Solheim, Ksenia; Mellemsether, Beate (Frontiers in Education, 2025)
IntroductionInclusive education requires not only systemic change but also direct attention to the classroom experiences of minority students. This study investigates how instructional and emotional support from teachers influence minority students’ perceptions of inclusivity and their academic and emotional engagement.MethodsA mixed-methods approach was employed, involving survey responses from 305 minority students and participant observations across multiple educational settings. Quantitative data were analyzed to identify correlations, while qualitative observations provided contextual depth.ResultsApproximately 7% of students reported receiving little to no instructional or emotional support from teachers. Quantitative analysis revealed significant positive correlations between the level of perceived support and students’ academic engagement and emotional well-being. Observational data reinforced these findings by highlighting inconsistencies in inclusive practices across classrooms.DiscussionThe findings underscore the critical role of both emotional and instructional support in fostering inclusive learning environments. The study advocates for a redefinition of inclusive education that explicitly integrates these support dimensions. It further recommends targeted teacher training and systemic policy interventions to bridge identified gaps and promote equitable learning outcomes for minority students.